👤
a fost răspuns

AJUTATIMA CAT MAI REPEDE!! URGENT!! 
a) 6√7 + 3(√3 - 2√7);
b) 2(5√3 + 3√2) - 10√3;
d) 3· (2√7 - 3√3) - √252;
f) 8(4√3 - 6√6) + 4· (12√6 - 7√3) .
 VA ROG TARE MULT !! URGENT!!



Răspuns :

a) √7 + 3√3 - 6√7 = 3√3 - 5√7
b) 10√3 + 6√2 - 10√3 = 6√2 , s-au redus 10√3 cu - 10√3
d) 6√7 - 9√3 - √252 = 6√7 - 9√3 - √2²·3²·7 = 6√7 - 9√3 - 2·3√7 = 6√7 - 9√3 - 6√7
                             = - 9√7,  √252 il descompui in factori primi, adica
                                           252 = 2²·3²·7
f) 32√3 - 48√6 + 48√6 - 28√3 = 4√3